ANALYSIS OF THE USE OF GOOD AND CORRECT INDONESIAN LANGUAGE IN THE SIMAMA 2024 DOCUMENT - Ertinawati, Yuni; Hasya, Azka Hijran; Khoerunnisa, Intan; Salma, Putri Nabila; Anjani, Syalsa Dwi (Media Inovasi Pendidikan dan Publikasi, 2024)
Language is a sound produced by the human vocal tract, not a sound produced by other organs. Using good and correct Indonesian can be interpreted as using a variety of languages ​​that are in harmony with the target and which in addition follows the correct language rules (Alwi, et al., 2010). Good Indonesian is language that is used according to the situation and conditions that include 4 aspects, namely place, time, language actors and purpose. Correct Indonesian is language that is used according to language rules consisting of spelling rules, phonological rules, morphological rules, syntactic rules, semantic rules, paragraph rules, discourse rules, and logical rules. The importance of using Indonesian in accordance with applicable grammar and spelling rules not only affects the effectiveness of communication, but also the formation of national identity and national culture. Mistakes in the use of language can interfere with understanding, damage credibility, and reduce the quality of information delivery. The use of Indonesian is very important in writing letters because it ensures that the message to be conveyed can be clearly understood by the recipient of the letter. The use of standard Indonesian ensures uniformity in communication. Using Indonesian in notification letters is a form of respect for the national language and national identity.